Em direção a uma metodologia para o desenvolvimento de frameworks de aplicação orientados a objetos - Pereira e Silva, Ricardo; Price, Roberto Tom (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24451, 1996)
The analisys of some framework development methodologies, shows the lack of modeling techniques and a detailed development process. In contrast, this features are contained in most object-oriented application development methodologies. Starting with analisys of these methodologies, is discussed how to adapt their modeling techniques to be used in frameworks development. The perceived need is to extend the static modeling techniques with class and method categorization, and to stress the use of colaborations for the dynamic modeling.